Cartas para Amazônia: convergências entre saberes locais e Ensino Superior - SILVA, Aldenora Pena da (Universidade Federal do Pará, 2023)
Traveling through the various sides of Amazon region is the invitation of this present The present paper. The objective of the research is to contribute to the promotion and appreciation of Amazonian identities in teaching and learning processes experienced by undergraduate students from the North Region of Brazil. In this regard I intend to promote discussions through the convergence between the local knowledge and higher education. The Pedagogical Letters are used in this research as a methodological support for those discussions and to increase connections among students from different realities and different places in Amazon region by reviewing their surroundings, sharing impressions, and identifying themselves in the eyes of others based on differences and similarities. The purpose is to initiate a journey guided by various theories which support this research. The journey begins with the theoretical-methodological proposal by Jesús Martín-Barbero (2004), supported by Deleuze and Guattari (2000) and Passos, Kastrup and Escóssia (2015), such theorists identified in the cartography as a study perspective opened to different views that enable the researcher being part of the research by affecting and being affected by those experiences. Paulo Freire thoughts are present as a methodological tool in the Pedagogical Letters and in the claimed theories of a transformative, critical and emancipatory education. To substantiate the discussion on identity the theories of Stuart Hall (2005), Néstor Canclini (2008), Rogério Haesbaert (2010), Silva (2012) and Oliveira (2019) contribute to the understanding of the confusing ways of the Amazon formation. The discussion on higher education institutions is supported by the theories of Mello (2007) and Mello, Almeida Filho and Ribeiro (2008). It is not possible to develop a research on pedagogical letters without mentioning Wolton (2006), Freire (1985), Amabile (2012) and Paulo e Dickmann (2020) and the concepts that permeate the paths of communication, creativity and intentionality in the exchanged letters. Supported by such theoretical-methodological foundations, we developed the educational product Cartas para Amazônia, which is composed for a) Travel Kit: that brings clues on how the exchange of correspondences can occur methodologically and b) Travel Diary: from the research experienced by me and the students-correspondents and from discoveries and the connections among different worlds and knowledges the final educational product – Collection of Letters – Cartas para Amazônia rises. The exchange of letters proposes to bring, to each of the student-correspondents, the intersection between local and academic-scientific knowledge, enabling a diferente view of their own reality by sharing with others their conceptions of what associates them with this place in the world, appreciating their identity relationship and promoting practices engaged linked with the preservation and appreciation of Amazon.